prove

Asked by  | 24th Apr, 2008, 06:59: PM

Expert Answer:

tan2A - sin2A =tan2A . sin2A

RHS

sin2A/cos2A --sin2A

= sin2A -- sin2A. cos2A  /  cos2A

=sin2A ( 1- cos2A )  / cos2A

=tan2A . sin2A   LHS

 

1+ sin A /1 - sin A =( sec A + tan A)2

RHS

( 1 + sin A) ( 1+ sin A) /  1 -- sin2A

= ( 1 + sin A )2 / cos2A

=1 + sin2A + 2 sinA / cos2A

=1/cos2A  +  sin2A /  cos 2A+ 2 sin A/ cos A   .1/cosA

=sec2A  + tan2A  + 2 tan A sec A

= ( sec A + tan A )2

 

 

Answered by  | 24th Apr, 2008, 11:28: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.